Changes in Knowledge and Attitudes in Preventing Anemia in Female Adolescents: A Comparative Study - Nur Intan Kusuma; Farida Kartini (Women, Midwives and Midwifery, 2021)
Background: Anemia in adolescents is a global health problem, with prevalence in Southeast Asia reaching 27% -55% and 37.1% in Indonesia. Anemia in adolescents entails a negative impact, including fatigue, decreased concentration, growth problems, and long-term causes of anemia during pregnancy. Therefore, health education regarding anemia in adolescents is an effort to prevent and diminish the prevalence of anemia and anemia during pregnancy. Purpose: This study aims to describe adolescents' changes in knowledge and attitudes in preventing anemia after being treated with health education. Methods: This study employed a quasi-experimental design using a pretest-posttest technique with the control group. Samples were obtained through the total sampling of 20 female students as the experimental and 19 students as the control group. Data analysis used the Wilcoxon tests. Results: This study indicated the p-value of the knowledge variable p = 0.002 and the attitude variable p = 0.001 (<0.05). Conclusion: There is a change in educating female adolescents about anemia on knowledge and attitudes in preventing anemia. Health workers and schools are urged to improve adolescent reproductive health promotion, especially regarding anemia in female adolescents and its prevention.